2007
DOI: 10.1111/j.1460-9568.2007.05554.x
|View full text |Cite
|
Sign up to set email alerts
|

The phagocytic capacity of neurones

Abstract: Phagocytosis is defined as the ingestion of particulates over 0.5 microm in diameter and is associated with cells of the immune system such as macrophages or monocytes. Neurones are not generally recognized to be phagocytic. Using light, confocal, time-lapse and electron microscopy, we carried out a wide range of in-vitro and in-vivo experiments to examine the phagocytic capacity of different neuronal cell types. We demonstrated phagocytosis of material by neurones, including cell debris and synthetic particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 44 publications
2
33
2
Order By: Relevance
“…It may, however, seem unusual to assume a phagocytosis-like fusion role of neurons toward microglia. Nevertheless, different phagocytotic manifestations were observed in neurons (Bowen et al 2007), and interestingly, traces of apoptotic T cells were also found inside the perikaryon of facial motor neurons (Flügel et al 2000). In addition, unlike OX42-positive microglia, in the present study ED1-positive macrophages were not easily identified.…”
Section: Discussioncontrasting
confidence: 48%
“…It may, however, seem unusual to assume a phagocytosis-like fusion role of neurons toward microglia. Nevertheless, different phagocytotic manifestations were observed in neurons (Bowen et al 2007), and interestingly, traces of apoptotic T cells were also found inside the perikaryon of facial motor neurons (Flügel et al 2000). In addition, unlike OX42-positive microglia, in the present study ED1-positive macrophages were not easily identified.…”
Section: Discussioncontrasting
confidence: 48%
“…A partial defect in RBC phagocytosis might lead to older cells with membrane defects in the circulation. In the brain, microglia are the major phagocytic cells, but neurons have also been reported to carry out phagocytosis (4). While the mechanism is not yet entirely clear, microglia have been implicated in neuronal loss in a number of neurodegenerative disorders (reviewed in reference 33), raising the possibility that a partial defect in microglial phagocytosis might be responsible for the brain pathology observed for chorea-acanthocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…The highest expression of P2X7 receptors is on professional phagocytes of monocyte/macrophage lineage including microglia (10), but P2X7 also has ubiquitous distribution, and other cell types (e.g. epithelial and both mature and progenitor neuronal cells) are able to recognize and engulf apoptotic cells at slower rates (11)(12)(13). Apart from certain complement components (14), physiological regulators in the process of non-inflammatory removal of apoptotic cells have yet to be identified.…”
Section: Rapid Phagocytosis Of Non-opsonized Particles Including Apopmentioning
confidence: 99%